Phylogenetic analysis of the promoter element 2 of paramyxo- and filoviruses - Ashida, Shoichi; Kojima, Shohei; Okura, Takashi; Kato, Fumihiro; Furuyama, Wakako; Urata, Shuzo; Matsumoto, Yusuke (Microbiology spectrum, 2024)
The genomic intricacies of paramyxo- and filoviruses are highlighted by the bipartite promoters—promoter element 1 (PE1) and promoter element 2 (PE2)—at their 3 ' termini. The spacer region between these elements follows the “rule of six,” crucial for genome replication. By a comprehensive analysis of paramyxoviral genome sequences, we identified distinct subcategories of PE2 based on C and CG repeats that were specific to Orthoparamyxovirinae and Avulavirinae / Rubulavirinae , respectively, mirroring their evolutionary lineages. Notably, the PE2 of Rubulavirinae is integrated into the gene-coding region, a unique trait potentially linked to its strict dependence on RNA editing for virus growth. This study also focused on the PE2 sequences in filovirus genomes. The strict conservation of the continuity of UN 5 among virus species emphasizes its crucial role in viral genome replication.